EFFECTIVE APPROACHES TO CHARACTER EDUCATION: A LITERATURE REVIEW - Eka Sartika; Al-Amin (CV. ADIBA AISHA AMIRA, 2025)
This study aims to identify the most effective approaches in character education based on a review of existing literature. The main findings show that character education programmes that integrate the teaching of moral values with daily practices in the school environment tend to produce more significant impacts. In addition, collaboration between teachers, students and parents strengthens the effectiveness of such programmes through consistency of value reinforcement across different contexts. Continuous training for teachers on integrating character education in the curriculum also proved important. The study also highlights the need for continuous evaluation and adjustment to maintain the relevance and effectiveness of the programme. With a holistic, consistent and collaborative approach, character education programmes can achieve optimal results in shaping students' character.